(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article system research of addressee sintaxem modern literary Ukrainian is conducted on material of texts of different styles in connection with the semantic and valency types of predicates. The semantic variants of category of addressee are described in the elementary and unelementary simple sentences, its lexical filling. The methods of complication of addressee semantics are definited by other values.